2016
DOI: 10.1038/srep23328
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell lineage tracking analysis reveals that an established cell line comprises putative cancer stem cells and their heterogeneous progeny

Abstract: Mammalian cell culture has been used in many biological studies on the assumption that a cell line comprises putatively homogeneous clonal cells, thereby sharing similar phenotypic features. This fundamental assumption has not yet been fully tested; therefore, we developed a method for the chronological analysis of individual HeLa cells. The analysis was performed by live cell imaging, tracking of every single cell recorded on imaging videos, and determining the fates of individual cells. We found that cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 25 publications
(32 reference statements)
6
78
0
Order By: Relevance
“…We created a cell-lineage database and maps based on the tracking data, and found that the fates of the A549 cells varied (see Figs. S1-4), as shown previously for cervical cancer-derived HeLa cells (15).…”
Section: Single-cell-lineage Tracking Analysis Of P53 Gene-silenced Asupporting
confidence: 82%
See 1 more Smart Citation
“…We created a cell-lineage database and maps based on the tracking data, and found that the fates of the A549 cells varied (see Figs. S1-4), as shown previously for cervical cancer-derived HeLa cells (15).…”
Section: Single-cell-lineage Tracking Analysis Of P53 Gene-silenced Asupporting
confidence: 82%
“…We previously developed a novel, chronological, single-cell-lineage tracking system to analyze heterogeneity among cultured cells at the single-cell level by continuous recording of cellular events and movements of live cultured cells using differential contrast imaging (DIC) (15). Resulting live cell imaging videos, which contained multidimensional information, including morphology of cells, position of individual cells within a cell population and types of cellular events occurred in a cell.…”
Section: Introductionmentioning
confidence: 99%
“…Differential interference contrast (DIC) images (2 3 2 FOVs) were taken every 5 min with an Uplsapo Super Apochromat (Olympus) 310 the dry objective (numerical aperture, 0.4), with a 31.5 coupler using near-infrared lightemitting diode (pE-100, 740 nm; CoolLED, Andover, United Kingdom). Cell tracking was performed for 300 min after 10 h of differentiation, as previously reported by Sato et al (29). Briefly, 100 cells were individually tracked, and the moving distances at each time point were calculated by the positions of the cells at each time point with in-house software.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
“…In this context, lineage mapping refers to the tracking of both cell position and cell division into progeny within the developmental stage of a living organism. While canonical cell lineage mapping has been determined for simpler organisms such as Caenorhabiditis elegans , modern lineage mapping is nevertheless an active field of research for more complex organisms as well as for the analysis of mutant phenotypes and other more in‐depth investigations (Amat et al., ; Chalfoun et al., ; Christensen et al., ; Heid, Voss, & Soll, ; McDole et al., ; Sato, Rancourt, Sato, & Satoh, ; Stegmaier et al., ; Tassy, Daian, Hudson, Bertrand, & Lemaire, ; Winter et al., ).…”
Section: Analysis and Modeling Of Tracking Datamentioning
confidence: 99%